LONGITUDINAL ELLIPSOID ZONE AND OUTER RETINAL INTEGRITY DYNAMICS AFTER EPIRETINAL MEMBRANE SURGERY. Issue 2 (February 2022) - Tuifua, Tisileli S.; Abraham, Joseph R.; Srivastava, Sunil K.; Kaiser, Peter K.; Reese, Jamie; Ehlers, Justis P.
Abstract : Purpose: To quantify ellipsoid zone (EZ) changes in integrity after epiretinal membrane (ERM) surgery, correlate findings to visual acuity, and determine predictors for prognosis. Methods: A post hoc analysis of eyes undergoing ERM surgery pooled from the prospective DISCOVER intraoperative optical coherence tomography study and eyes undergoing conventional ERM surgery without intraoperative optical coherence tomography. Quantitative EZ features were extracted using a multilayer machine learning enabled automated segmentation platform after image analyst review/correction for segmentation accuracy. Visual acuity and EZ integrity were quantitatively assessed and correlated before and after ERM surgery. Multiple linear regression was performed to assess preoperative visual acuity and EZ features as predictors for improvement in visual acuity or EZ integrity. Results: There were 177 eyes from 177 subjects that underwent ERM surgery from the DISCOVER and conventional arms. Improvement in visual acuity and multiple EZ integrity features was noted after ERM surgery, including EZ partial attenuation and EZ-retinal pigment epithelium (RPE) volume ( P < 0.05). A reduction in EZ partial attenuation and increase in EZ-RPE central subfield thickness (EZ-RPE CST) was significantly correlated with improved visual acuity after ERM surgery ( P < 0.05). More robust EZ-RPE CST at baseline predicted visual acuity improvement after ERM peel in regression modeling (β = 0.005, P < 0.05). Conclusions: Longitudinal assessment of EZ features demonstrates significant postoperative improvement in multiple EZ integrity metrics after ERM surgery. Improving EZ integrity was correlated to improving the visual acuity. Ellipsoid zone integrity and visual acuity were significant predictors in regression modeling and may have value in clinical prognostication.